Student protests in Chile (2011)
ABSTRACT: The newspaper The New York Times considered that the Chilean student movement, that demands deep changes to the education, is comparable with the wave of popular rises that began in Tunisia and that it was baptized like the “Arab spring”. August 5´of 2011.